Photo-oxidative degradation of bisphenol A by H2O2/UV: process study and kinetic modelling. - Araujo, Leandro Goulart de (2018)
Bisphenol A (BPA) is widely used in the production of plastics, epoxy resins and polycarbonates. It is a toxic, endocrine disruptor compound. Different studies have shown the presence of BPA in several environmental systems, classifying it as a worldwide persistent pollutant which may act synergistically with other pollutants. In this context, advanced oxidation processes (AOP) have received great attention due to their ability to degrade pollutants with such characteristics, through their transformation into less hazardous compounds or even their mineralization. Although there are investigations on the use of AOPs for BPA degradation, systematic studies on the effects of process variables, coupled with the statistical interpretation of the results are virtually non-existent. Furthermore, to the best of our knowledge, a rigorous kinetic model has not yet been proposed for the degradation of this pollutant by the H2O2/UV process. The objective of this work was to evaluate BPA degradation by the H2O2/UV process, investigating the effects of the initial H2O2 concentration and the specific rate of photons emission (EP,0) by means of a Doehlert experimental design, combined with the response surface methodology. The experiments were performed in a photochemical tubular reactor equipped with a 254-nm UV lamp, for [H2O2]0 and EP,0 in the ranges 1.6-9.6 mmol L-1 and 0.87 × 1018-3.6 × 1018 photons L-1 s-1, respectively. Total BPA degradation was achieved after 60 min of irradiation in all experiments. The best conditions were [H2O2]0 = 7.6 mmol L-1 and EP,0 = 3.6 × 1018 photons L-1 s-1, for which the best performance was obtained regarding the BPA degradation rate, BPA degradation after 15 min, and the second highest TOC removal after 180 min. However, in most experiments less than 75% TOC removal was observed, with 95% mineralization obtained only for the superior [H2O2]0 and EP,0. A mathematical model was developed, considering the reactor characteristics and the radiation field, based on the line source with parallel emission (LSPP) approach, in combination with the radiative transfer equation (RTE), mass balances, and a detailed kinetic model of the H2O2/UV process. The steady-state approximation was applied for all radical species. In the estimation of unknown kinetic constants, the non-linear least squares method was employed. The model was able to satisfactorily fit experimental BPA and H2O2 concentrations as a function of time. This work shows that the H2O2/UV process is a good alternative for BPA removal from aqueous streams, with total degradation of the target compound and adequate percent mineralization under optimal operating conditions. Such conditions may serve as first guidelines for pilot-plant and industrial processes operation. In addition, simulations using the proposed kinetic model may provide useful information for the design and scale-up of pre- or post-treatment of effluents containing this pollutant.